Risk Factors for Work Fatigue in Welding Workers in the Oil and Gas Industry: Literature Review - Ridho Pradana Mahaputra; Baiduri Widanarko (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Welding workers in the Oil and Gas Industry are often exposed to heat sources such as sunlight and welding machines, especially when working outdoors. The welding process involves cutting, heating, grinding, joining, painting, and sanding, which can lead to significant fatigue, impacting their health and safety. Objective: Workers who do welding are often exposed to heat sources, including sunlight and heat from welding machines because some employees do welding outdoors. Cutting iron, heating, grinding, joining, painting, and sanding are steps in the welding process carried out in a work environment exposed to sunlight. Thus, is fatigue a risk for welding workers in the Oil and Gas Industry. This study aims to determine the level of risk of causing work fatigue in welding workers in the Oil and Gas Industry. Method: This study is a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) method. Literature searches were obtained from Google Scholar, Science Direct, and Neliti Jurnal. The keywords